The readiness level of using e-learning among Teacher Graduate Programme (TGP) - Abd Samad, Noorazman; Wan Ahmad, Wan Mohd Rashid; Harun, Hairuddin; Mohd. Noor, Siti Noor Fazelah; Ismail, Affero; Abd. Rahman, Mohd Wafi; Justin, Randy (EDP Sciences, 2018)
Using e-Learning among Teacher Graduate Programme (TGP) to students who are newly exposed in Teaching and Learning (T&L) proses. The major problem among student’s TGP is the readiness level in knowledge, attitude and skills using e-Learning during Teaching and Learning (T&L) . This study is to identify any significant differences of the knowledge level between male and female TGP students. The design of this study is to survey research using instruments of questionnaire which are distributed to respondents among TGP students at the Faculty of Technical and Vocational, UTHM. The sample is given to 248 respondents and analysis using version SPSS 21.0. Data presented using descriptive method such as, Mean, Standard Deviation(SD), inferens statistic using Mann-Whitney U to identify the knowledge difference between male and female TGP students. The result showed that the level of application of e-Learning among TGP students in terms of knowledge, attitude and skill at moderate level. The study also showed that there are no significant knowledge difference among male and female TGP students because the result of p= 0.044 value is less <0.05 can be stated that Ha failed rejected. The results of this study is important to provide awareness especially to the TGP students, lecturers and also UTHM in providing new T&L using eLearning.